Technical Note: Influence of entrance window deformation on reference dosimetry measurement in various beam modalities. Issue 2 (26th December 2018) - Kinoshita, Naoki; Kohno, Ryosuke; Oguchi, Hiroshi
Abstract : Purpose: Phantoms for horizontal beam geometry can avoid issues in vertical‐beam geometry, such as change in chamber depth due to evaporation, and defining the origin at the water surface. However, their thin entrance windows would deform when these phantoms are filled, which can change the chamber depth, as pointed out by The International Atomic Energy Agency (IAEA) TRS‐398. Currently, few reports (Arib et al., J Appl Clin Med Phys . 2006; 7 :55–64, and Kinoshita et al., Rep Pract Oncol Radiother . 2018; 23 :199–206) are available with practical data on window deformation. Therefore, we investigated the influence of entrance window deformation on chamber depths in water phantoms and the measurements in various beam modalities. Methods: To examine widely used phantoms and phantoms with different characteristics, three phantom types were investigated (the number of phantoms investigated appears in parentheses): PTW—type 41023 (2), Qualita—QWP‐04 (2), and IBA—WP34 (2). Prior to the investigation, these phantoms were stored for acclimatization in a room for approximately 10 h under the following two conditions: (a) room temperature: 21 ± 2°C; (b) room temperature: 27 ± 2°C. Using a dial indicator, the centers of the windows were monitored every 30 min for 12 h immediately after the phantoms were filled, in a treatment room at the room temperature of 21 ± 2°C. Results: Immediately after the phantoms were filled, the window deformation ranged from −0.07 (inward‐deformation) to 0.3 mm (outward deformation) among the six phantoms, in comparison with empty phantom windows. For 12 h after the phantoms were filled, the change in the deformation was up to 0.23 mm, but typically less than 0.15 mm. Conclusions: Reference dosimetry in photon, electron, and proton beams would not be influenced significantly by these window behaviors, whereas the window deformation has a slight impact on those heavy ion beams.